(untitled) (Orfeu, 2022)
This work is an excerpt of a complete research at the master’s level that had as its object of study the musicobiographization processes of music teachers from their research carried out in the master’s degree. The main objective of the research is to understand how these professionals have been reconfiguring themselves with their research in music-educational practices. The theoretical framework was centered on Paul Ricoeur’s theory of the triple mimesis – prefiguration, configuration and refiguration – in time and narrative, used in the research analysis process as well. The approach used was the (auto)biographical research whose source was the Narrative (Auto)Biographic Interview. For this article, an analytical synthesis of the objective research was highlighted, outlining a comprehensive synthesis of the concept of musicobiographization that were presented with emphasis on the research regarding the concept of biographization. Upon completing a survey, I understood three search co-participates engender a reconfigured life-formation. Thus, narrative reflexivity constitutes a potential force that generates impacts on the musician-educational practices of professionals.